Challenges and Thoughts on Risk Management and Control for the Group Construction of a Super-Long Tunnel by TBM. (February 2018) - Deng, Mingjiang
Abstract: The total length of the second stage of the water supply project in the northern areas of the Xinjiang Uygur Autonomous Region is 540 km, of which the total length of the tunnels is 516 km. The total tunneling mileage is 569 km, which includes 49 slow-inclined shafts and vertical shafts. Among the tunnels constructed in the project, the Ka–Shuang tunnel, which is a single tunnel with a length of 283 km, is currently the longest water-conveyance tunnel in the world. The main tunnel of the Ka–Shuang tunnel is divided into 18 tunnel-boring machine (TBM) sections, and 34 drilling-and-blasting sections, with 91 tunnel faces. The construction of the Ka–Shuang tunnel has been regarded as an unprecedented challenge for project construction management, risk control, and safe and efficient construction; it has also presented higher requirements for the design, manufacture, operation, and maintenance of the TBMs and their supporting equipment. Based on the engineering characteristics and adverse geological conditions, it is necessary to analyze the major problems confronted by the construction and systematically locate disaster sources. In addition, the risk level should be reasonably ranked, responsibility should be clearly identified, and a hierarchical-control mechanism should be established. Several techniques are put forward in this paper to achieve the objectives mentioned above; these include advanced geological prospecting techniques, intelligent tunneling techniques combined with the sensing and fusion of information about rock parameters and mechanical parameters, monitoring and early-warning techniques, and modern information technologies. The application of these techniques offers scientific guidance for risk control and puts forward technical ideas about improving the efficiency of safe tunneling. These techniques and ideas have great significance for the development of modern tunneling technologies and research into major construction equipment.